Gender Relations in Famale Leadership: an Empirical Study of Famale Judges in Religious Courts in South Sulawesi - Nisa'ul Majdah Nurdin; Andi Mutmainnah Assyahrah; Kurniati Kurniati (Insight: Indonesian Journal of Social, Humanity, and Education, 2026)
Women's leadership in Islamic judicial institutions is a contemporary issue that requires in-depth study from the perspective of Islamic law and social reality. This study examines three fundamental aspects: Islamic law's view of women's leadership in religious courts, perceptions of the legitimacy of female judges' leadership, and gender challenges faced in judicial practice in the South Sulawesi Religious Court. The method used is normative legal research (library research) with a conceptual and case approach, analyzing primary legal sources such as the Qur'an, hadith, and religious court regulations, as well as secondary sources such as academic literature and previous research results. The results of the study show that Islamic law does not absolutely prohibit female leadership in the judiciary, with contextual interpretations of Sharia arguments that consider Sharia objectives and maslahah. However, the perception of the legitimacy of female judges is still influenced by patriarchal gender constructs rooted in conservative interpretations of religious texts. The main challenges include the theological dimension of resistance based on hadith prohibiting female leadership, the structural dimension of gender bias in the promotion and assignment system, and the socio-cultural dimension of the double burden of domestic and public roles. This study contributes to the development of a progressive Islamic legal discourse that supports gender equality in religious court institutions in Indonesia.